The Impact of SIMEDHI on the Performance and Competency of Industrial Relations Mediators through Data Accuracy as Mediation - Nadin, Hasdin; Kisman, Zainul; Bastaman, Aam; Ramayanti, Rizka (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2025)
This study aims to analyze the effect of implementing the Industrial Relations Mediator Information System (SIMEDHI) on performance assessment and competency improvement of Industrial Relations Mediators, with data accuracy as a mediating variable. Using a quantitative approach and survey method, data were collected through questionnaires distributed to 205 mediators across various provinces in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that SIMEDHI significantly affects data accuracy. Furthermore, data accuracy acts as a significant partial mediator between SIMEDHI and both mediator performance and competency. These findings highlight that accurate information systems strengthen decision-making in performance evaluation and support data-driven competency development programs.